Gambaran Health literacy fungsional, komunikatif, dan kritikal pada pasien Stroke di RSUD Haji Makassar - Nurul Fadhilah Gani; Junaiddin Junaiddin (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2020)
Health literacy is the ability of every individual to access, understand, and make decisions related to information and health services in making health care decisions. health literacy associated with patient health status. The aim of the research was to determine the description of health literacy functional, communicative, and critical in stroke patients at Haji Hospital Makassar.The research used survey design. The sample consisted of 30 people selected using accidental sampling technique. The data were analyzed using frequency distribution to describe each variable. The Results of the research indicate that based on all types of health literacy that are functional, communicative and critical health literacy, majority of the respondents are less good. Therefore,we need to improve the patient's health literacy to support the health care process. Keywords: health literacy, functional, communicative, critical, stroke.